EPCO-12. STING IS SILENCED IN GBM BY PROMOTER METHYLATION THAT IS ESTABLISHED BY TISSUE OF ORIGIN. (12th November 2021) - Low, Justin; Chandramohan, Vidyalakshmi; Bowie, Michelle; Brown, Michael; Waitkus, Matthew; Briley, Aaron; Stevenson, Kevin; Fuller, Rebecca; Reitman, Zachary; Muscat, Andrea; hariharan, Seethalakshmi; Hostettler, Janell; et al.
Abstract: STING (Stimulator of interferon genes) is an initiator of endogenous antitumor immunity. Loss of STING expression has been observed in various cancer types. Here we describe a mechanism of STING suppression that is common to brain tumors, occurring through regional promoter hypermethylation (RPH) near its transcriptional start site. The RPH-mediated suppression of STING expression is selective to normal brain and neuroectoderm-derived tumors, but not present in most other tumor types and cells in the brain tumor microenvironment. A pan-cancer comparison revealed that STING RPH levels in tumors correlate with the respective tissue of origin, including tumors metastasizing to the brain. We demonstrate that STING RPH suppression in glioma cells may be reversed by treatment with decitabine, a DNA methyltransferase inhibitor that is used in the treatment of hematologic malignancies. Collectively, our results suggest that the epigenetic silencing of STING occurs early in brain development and may provide an immunosuppressive context for the genesis of brain tumors. Furthermore, our findings that STING suppression in brain tumor cells can be reversed by epigenetic modulation have significant therapeutic implications for the treatment of glioblastoma and potentially other STING-silenced, immunologically-cold cancers.